2013
DOI: 10.1186/1471-2229-13-40
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of tomato pre-abscission pedicels provides insights into abscission zone properties including competence to respond to abscission signals

Abstract: BackgroundDetachment of plant organs occurs in abscission zones (AZs). During plant growth, the AZ forms, but does not develop further until the cells perceive abscission-promoting signals and initiate detachment. Upon signal perception, abscission initiates immediately; if there is no signal, abscission is not induced and the organ remains attached to the plant. However, little attention has been paid to the genes that maintain competence to respond to the abscission signal in the pre-abscission AZ. Recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 96 publications
(128 reference statements)
9
75
0
Order By: Relevance
“…The increasing expression of the genes coding for ET biosynthesis enzymes, the increase in the ACC content, as well as studies of ACC immunolocalization in the abscission zone, all suggest that ethylene is directly involved in the functioning of the flower abscission zone in L. luteus. This hypothesis was also confirmed by the results of research performed in other plant species, in which the factors activating abscission of particular organs stimulate the expression of both ACC synthases and oxidases, e.g., in apple (MdACO3, MdACO4, MdACO1) or tomato (SlACO5, LACS2) [41][42][43][44]. Moreover, it was found that immediately before flower abscission in Ecballium elaterum and S. lycopersicum [45,46], the ethylene production rate increases.…”
Section: Discussionsupporting
confidence: 61%
“…The increasing expression of the genes coding for ET biosynthesis enzymes, the increase in the ACC content, as well as studies of ACC immunolocalization in the abscission zone, all suggest that ethylene is directly involved in the functioning of the flower abscission zone in L. luteus. This hypothesis was also confirmed by the results of research performed in other plant species, in which the factors activating abscission of particular organs stimulate the expression of both ACC synthases and oxidases, e.g., in apple (MdACO3, MdACO4, MdACO1) or tomato (SlACO5, LACS2) [41][42][43][44]. Moreover, it was found that immediately before flower abscission in Ecballium elaterum and S. lycopersicum [45,46], the ethylene production rate increases.…”
Section: Discussionsupporting
confidence: 61%
“…These include homologs of AT2G43890, AT3G07970 (Fig. 9), and AT3G59850, which were previously found overexpressed in Arabidopsis and tomato pedicel AZs (Kim and Patterson, 2006;González-Carranza et al, 2007;Nakano et al, 2013). In parallel with the expression of cell wallmodifying enzymes, we also identified several genes associated with senescence, response to dehydration, and desiccation (Table III), which is consistent with pedicel drop.…”
Section: Az Development Is Controlled By a Complex Gene Networksupporting
confidence: 76%
“…We found that genes involved in the stress response were largely induced in L1 pedicels, indicating an activation of protection systems during abscission. The expression of chitinase B1 (CHIB1) and allergen family proteins in the AZ had previously been reported in tomato (Nakano et al, 2013) and Sambucus nigra (Ruperti et al, 1999), respectively. Consistent with the observed fruit growth arrest, genes involved in sugar synthesis and transport were also down-regulated in L1 pedicels throughout the three phases investigated.…”
Section: Az Development Is Controlled By a Complex Gene Networkmentioning
confidence: 88%
“…This set of cellular characteristics is reminiscent of meristematic tissues. Several genes involved in SAM maintenance and the initiation of axillary meristems are expressed in the AZ (Shi et al, 2011;Nakano et al, 2013;Wang et al, 2013). Therefore, it has been proposed that AZ cells have a meristematic identity.…”
Section: Osh15-qsh1 Dimer Functions For Az Developmentmentioning
confidence: 99%